The informality in Peru’s public employment system and the effectiveness of State measures adopted in response - Huamán Ordóñez, Luis Alberto (2024)
Informality is conceived as a social phenomenon and legally reprehensible, as it does not align with the standards of good coexistence within the community, and is perceived, from this perspective, as contrary to the rationality of the Western world. However, beyond these considerations, which are not always acceptable and involve more of a value judgment than an objective reality, this phenomenon is a response to the various contexts citizens face. Among these, it stands out as a means of adaptation to state rules. Typically, the concept of informality is linked to the private sector. However, against all expectations, informality is also present in the public sphere, particularly in the area of personnel provision within public-law organizations. In this context, the author focuses on analyzing the various concrete expressions that, within the Peruvian context, allow for the identification of informality. This is based on the idea that legal relationships concerning personnel are a key space where the state exploits service provisions for its own benefit using various legally reprehensible mechanisms, with the aim of disregarding the reality of proper administrative self-organization. The author concludes that the Peruvian state is a space where both formal and informal rules coexist, and significant governmental efforts are identified to self-limit such anomalous institutional practices.